2019
DOI: 10.1177/0023830919881479
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variation in West and East Coast African-American English Prosody and Rap Flows

Abstract: Regional variation in African-American English (AAE) is especially salient to its speakers involved with hip-hop culture, as hip-hop assigns great importance to regional identity and regional accents are a key means of expressing regional identity. However, little is known about AAE regional variation regarding prosodic rhythm and melody. In hip-hop music, regional variation can also be observed, with different regions’ rap performances being characterized by distinct “flows” (i.e., rhythmic and melodic delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(59 citation statements)
references
References 37 publications
1
58
0
Order By: Relevance
“…The present article is concerned with regional variation in African-American English (AAE) -specifically regarding its East Coast and West Coast regiolectsin the context of hip-hop culture. It examines AAE regiolects in a hip-hop context because the concepts of regional affiliation and identity are central to hip-hop culture, and because hip-hop aficionados -or "heads" (Alim, 2015) -purposely use their own regional accents of AAE to express their regional hip-hop identity (Forman, 2002;Gilbers, 2015Gilbers, , 2018aGilbers et al, 2019a;Hess, 2009;Morgan, 1993Morgan, , 1998Morgan, , 2001Morgan, , 2002. In light of this, and considering the longstanding rivalry between the East Coast and West Coast hip-hop communities, one can expect that speakers of these dialects immersed in hip-hop culture are more likely to use markedly regional accents than those who are not, making them optimal candidates to assess regional accent differences.…”
Section: Large Professormentioning
confidence: 99%
See 4 more Smart Citations
“…The present article is concerned with regional variation in African-American English (AAE) -specifically regarding its East Coast and West Coast regiolectsin the context of hip-hop culture. It examines AAE regiolects in a hip-hop context because the concepts of regional affiliation and identity are central to hip-hop culture, and because hip-hop aficionados -or "heads" (Alim, 2015) -purposely use their own regional accents of AAE to express their regional hip-hop identity (Forman, 2002;Gilbers, 2015Gilbers, , 2018aGilbers et al, 2019a;Hess, 2009;Morgan, 1993Morgan, , 1998Morgan, , 2001Morgan, , 2002. In light of this, and considering the longstanding rivalry between the East Coast and West Coast hip-hop communities, one can expect that speakers of these dialects immersed in hip-hop culture are more likely to use markedly regional accents than those who are not, making them optimal candidates to assess regional accent differences.…”
Section: Large Professormentioning
confidence: 99%
“…Regional differences that in retrospect were already apparent from the earliest studies on AAE were dismissed as incidental or irrelevant (Wolfram, 2007;Wolfram & Kohn, 2015). More recently, however, it was found that there are in fact regional differences between varieties of AAE spoken in the United States (e.g., Blake & Shousterman, 2010, Carpenter, 2004Childs & Mallinson, 2004;Childs, 2005;Cutler, 2007Cutler, , 2014D'Andrea, 2005;Gilbers, 2015Gilbers, , 2018aGilbers et al, 2019a;Green, 2002;Hinton & Pollock, 2000;Jones, 2015Jones, , 2020Mallinson & Wolfram, 2002;Mallinson, 2006;Morgan, 2001;Pollock & Berni, 1997;Rowe 2005;Wolfram, 2003).…”
Section: Large Professormentioning
confidence: 99%
See 3 more Smart Citations